2020
DOI: 10.1186/s12889-020-08484-0
|View full text |Cite
|
Sign up to set email alerts
|

Methods and design for the ADAPT study: Application of integrateD Approaches to understanding Physical activity during the Transition to emerging adulthood

Abstract: Background: The overarching objective of the study is to obtain a comprehensive understanding of the salient factors predicting changes in physical activity (PA) during adolescents' transition into emerging adulthood. Using the Multi-Process Action Control model as our guiding framework, we will examine how implicit and explicit psychological processes along with regulatory practices impact PA change during this major life transition. Additionally, we will use a real-time data capture method called Ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Data for the present study is from the baseline assessment from the ADAPT study (Kwan et al, 2020). The ADAPT study is a four-year prospective longitudinal study tracking a sample of Canadian adolescents as they transition out of high school and into emerging adulthood in order to gain an understanding of factors underlying changes in physical activity behaviour.…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for the present study is from the baseline assessment from the ADAPT study (Kwan et al, 2020). The ADAPT study is a four-year prospective longitudinal study tracking a sample of Canadian adolescents as they transition out of high school and into emerging adulthood in order to gain an understanding of factors underlying changes in physical activity behaviour.…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%
“…Parental consent collected by paper or electronically was also a requirement for their data to be included in the study. More information about the recruitment strategy and study protocol can be found in the methods paper (Kwan et al, 2020). The protocol for the ADAPT study was approved by both the Institutional Research Ethics Board and the School Board Ethics Committee.…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%
“…Kang and Lee applied a psychological factor-based physical activity program to the physical education class of junior high school and reported that this intervention was significant to promote physical activity participation and its related competence and enjoyment [ 37 ]. More recently, Kwan and the colleagues conducted systematic review and meta-analysis to identify the effect of psychological modification strategy on improving physical activity [ 38 ]. This study concluded that the strategy is effective at increasing the time spent on physical activity and energy expenditure in physical activity, using cognitive and behavioral strategies, and improving perceived benefits and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The present study utilized baseline data from the ADAPT study: Application of integrateD Approaches to understanding Physical activity during the Transition to emerging adulthood. 33 This is a four-year, prospective longitudinal study tracking a sample of Canadian adolescents as they transition out of high school and into emerging adulthood in order to gain an understanding of factors underlying changes in physical activity behaviour. At baseline, all grade 11 students enrolled into one of the seven secondary schools across a large school board in Southern Ontario were invited to take part in the study.…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%
“…More information about the recruitment strategy and study protocol can be found elsewhere. 33 The protocol for the ADAPT study was approved by both the Institutional Research Ethics Board and the School Board Ethics Committee. Among the 2412 enrolled at one of the seven secondary schools within the school board, 1585 agreed and provided consent to participate (66% response rate).…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%